The water dispatching of river basins during dry periods under the most stringent water management system in China - Yanhu He (IWA Publishing, 2021)
Since 2011, China has implemented its most stringent water management system to effectively protect water resources and guarantee socioeconomic development. More basin-scale water division schemes have been developed to act as references for basin-scale water resources management. Water dispatching during dry periods is an effective way to guarantee the water supply for the river basin, and is also an important component of basin-scale water resources management. Given this, the present study proposes a framework for the water dispatching of river basins during dry periods under the most stringent water management system in China. This framework mainly consists of the analysis and forecasting of rainfall and inflow, the dispatching requirements for the main water users, major reservoirs, and sections, as well as safeguard measures. The Jian River Basin in South China is presented as a case study. The total discharge of the Gaozhou Reservoir in 2017 was 25 million m3 more than the target discharge specified in the water dispatching scheme, and the total water storage utilization ratio during the dispatch period was 4.7% higher than the target utilization ratio. These factors demonstrate the effectiveness and applicability of the proposed framework. HIGHLIGHTS The proposed framework for the water dispatching of river basins during dry periods provides reliable technical support for water use security under the most stringent water management system in China, and is demonstrated to be both effective and applicable.;